PENINGKATAN HASIL BELAJAR MENULIS KARANGAN DESKRIPSI MENGGUNAKAN METODE KOOPERATIF CONCEPT MAPPING DI SD - Aprilianti, Rahmi; Kaswari, Kaswari; Tampubolon, Budiman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakThe purpose of this study is to describe the ability of teachers to design lesson plans, the ability of teachers to implement learning, and improving student learning outcomes in learning writing descriptive essay using cooperative model concept mapping in class 5A Primary School 73 Pontianak West. The method used in this research is descriptive method, the form of research that is action research class. The subjects of the study were 5A students who were 30 students. The results of the study as follows: The ability of teachers to design lesson plans in the cycle I is 2.7 and 2.84. In the second cycle increased to 3.2 and 3.42. The ability of teachers in implementing the average learning cycle I is 2.84. In cycle II average 3,5 and 3,3. Student learning outcomes cycle I average 76.1 and 79, while in the second cycle rose to an average of 80 and 81.9. The conclusion of this research, by using cooperative concept mapping method can improve writing skill description in 5th grade A student at SD Negeri 73 Pontianak West.Â Keywords: Learning Outcomes, Writing skill, Concept Mapping